2019
DOI: 10.1007/s12520-019-00911-7
|View full text |Cite
|
Sign up to set email alerts
|

New insights into Neolithic milk consumption through proteomic analysis of dental calculus

Abstract: There has long been debate over the origins of dairy consumption within European populations. Whilst it was previously assumed that lactase persistence (LP) was under positive selection following the advent of agriculture, recent genetic studies of prehistoric human remains have revealed LP may have only emerged in Europe in the last 4000 years. These findings stand in contrast to organic residue analysis of Neolithic pottery indicating the utilisation of dairy products, and zooarchaeological mortality profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 82 publications
(116 reference statements)
5
46
2
Order By: Relevance
“…1c, d and 2d, e). Its importance is further supported by recent findings of cattle milk proteins in the dental calculus of Early Neolithic individuals from the UK 51 .…”
Section: Discussionmentioning
confidence: 72%
“…1c, d and 2d, e). Its importance is further supported by recent findings of cattle milk proteins in the dental calculus of Early Neolithic individuals from the UK 51 .…”
Section: Discussionmentioning
confidence: 72%
“…This is close to or within the timescale for the emergence of agriculture. The milk-producing animals cow, sheep, and goat were all domesticated between 8,000 and 10,000 years ago [20], and paleoproteomic analysis of dental calculus has shown that humans were consuming milk, most likely as cheese or other fermented products, by 5,500 years ago [21]. Because our estimate for the age of the LAC gene introgression extends into the period of milk animal domestication, it is plausible that selection for the introgression was the result of human activity during production of a fermented milk product, such as cheese or kefir.…”
Section: Resultsmentioning
confidence: 99%
“…ß-lactoglobulin appears to be a relatively robust protein and has been identified in other Bronze Age and Neolithic samples, where total protein identifications were similar to those observed in this study. For example, even in relatively poorly preserved early Neolithic dental calculus samples from Britain (with total protein identifications ranging from 15 to 128 proteins), ß-lactoglobulin was detected in six of the 10 tested individuals [107].…”
Section: Plos Onementioning
confidence: 99%